Challenges and solutions for renewable energy storage - Santos, Diego Resende; Vieira, Eric Caetano Maurício; Rocha, Jessica Taveira da; Eugenio, Quéren Hapuque de Souza; Campos, Carlos da Mata (Brazilian Journal of Production Engineering, 2023)
Renewable energy storage systems face challenges related to capacity, efficiency, lifespan, and costs. Technologies such as batteries, hydro-pumping, thermal storage, and compressed air have capacity limitations and may require large areas. Energy losses during storage impact system efficiency, as well as degradation over time. High costs are also a concern. To overcome these limitations, investments in research and development, new materials, designs, and technology integration are necessary. Partnerships between governments, industry, and research institutions are important, as well as government policies and financial incentives. Case studies, like the Tesla Powerpack project in Ta'u Island, demonstrate the successful implementation of renewable energy storage systems. The objective of this article is to review the literature on ways to improve energy efficiency and reduce losses during renewable energy storage, highlighting associated features and challenges.
Keywords: Renewable energy; Storage; Sustainability